2016
DOI: 10.1097/aog.0000000000001338
|View full text |Cite
|
Sign up to set email alerts
|

Twin Pregnancy and Severe Maternal Outcomes

Abstract: Twin pregnancy is associated with greater severe maternal morbidity and a higher rate of maternal death than singleton pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 23 publications
3
45
1
1
Order By: Relevance
“…Previous studies reported an incidence of PPH in multiple pregnancy in the range of 3.4–24% [23, 24]. In our study, there was a significantly higher rate of PPH secondary to uterine atony in the mothers in the DCC group.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies reported an incidence of PPH in multiple pregnancy in the range of 3.4–24% [23, 24]. In our study, there was a significantly higher rate of PPH secondary to uterine atony in the mothers in the DCC group.…”
Section: Discussionsupporting
confidence: 64%
“…However, our current understanding of the underlying metabolic mechanisms leading to suboptimal growth remains limited. Selective intrauterine growth restriction (sIUGR) is one of the most serious complications of monochorionic diamniotic (MCDA) twins with an incidence of 10–25% 2 4 . Compared with singleton intrauterine growth restriction (IUGR), sIUGR presents higher risks of adverse pregnancy and postpartum outcomes for both the mother and offspring 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A total of 941 (88.6%) women who gave birth at MSCRH made at least one visit to an antenatal clinic and had laboratory procedures completed. In this study, a cut-off of <10 g/dl was used to define anaemia, which is one point below WHO standards (Santana et al, 2016). A total of 424 (45%) women had haemoglobin levels below the cut-off.…”
Section: Resultsmentioning
confidence: 99%